2014
DOI: 10.1111/eth.12327
|View full text |Cite
|
Sign up to set email alerts
|

Coloration, Paternity, and Assortative Mating in Western Bluebirds

Abstract: Coloration in birds can act as an important sexual signal in males, yet in many species, both sexes display bright colors. Social selection may account for this pattern, with more brightly colored individuals pairing together on the best territories. Mutual mate choice may also explain this, as males investing a great deal of parental care in the offspring should be choosy about their social mates. It is less clear whether this pattern of mate choice can apply to extra‐pair partners as well. We examined wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
(135 reference statements)
3
12
0
Order By: Relevance
“…2013; Jacobs et al. 2015; Charmantier et al. 2017), and many studies have compared CVs between traits with different dimensions or statistical distribution.…”
Section: Discussionmentioning
confidence: 99%
“…2013; Jacobs et al. 2015; Charmantier et al. 2017), and many studies have compared CVs between traits with different dimensions or statistical distribution.…”
Section: Discussionmentioning
confidence: 99%
“…My results are consistent with a previous study in western bluebirds that reported no relationship between female coloration and the rate of extra-pair paternity within broods (Jacobs et al, 2015). In contrast, female yellow warblers displaying plumage with greater melanin coverage, but lower carotenoid pigmentation had a higher proportion of extra-pair offspring in their broods compared to females with plumage that had both high melanin coverage and carotenoid pigmentation (Grunst and Grunst, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, it is also possible that the ornamentation of females is unrelated to the proportion of extra-pair paternity, as previously demonstrated in western bluebirds (Sialia mexicana; Jacobs et al, 2015).…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations